Full paying patient services in Malaysia: a counter-hegemonic response from a civil society organization / Mazlan Che Soh and Makmor Tumin - Che Soh, Mazlan; Tumin, Makmor (Universiti Teknologi MARA, 2022)
The movement of specialists from public hospitals to private hospitals is a major problem plaguing the government of Malaysia. In order to find a solution to this problem, the Malaysian government has taken many steps to reduce the migration of specialists, the Full Paying Patient Services (FPPS) scheme being one of those said steps. However, these measures have received a wide range of reactions from various parties, including civil society organizations (CSOs), which include the Coalition Against Healthcare Privatization (CAHP). This study aimed to examine the justification behind the government's implementation of these services, and to explain the responses of civil society organizations, thus providing a deeper understanding of CSOs responses toward governmental policies and initiatives. Employing Gramsci's counter-hegemony and Habermas' communicative rationality theory, and using CAHP as a case study, this study utilized a qualitative approach (through an interpretative lens), which benefited from secondary data as well as primary data through interviews. Besides that, this study revealed that, despite the many objections conveyed by the CSOs, many of them fell on deaf ears, and the efforts made by CSOs at best, were only able to delay the implementation of these services.